Reference service in branch libraries - Sity Norsimah Mohamed Darus. (2011)
This dissertation is an investigation into the provision of reference service in public branch libraries in Singapore. The focus of the study is to look into the perception towards the reference service from the perspectives of the library users and staff, and what can be done to improve the existing reference service provision. In particular, this study sought to find out what are the views or comments from the users and staff of the branch libraries if new reference service models, as highlighted in the literature, are adopted.